Personal and perceived stigma towards mental disorders among attendants of patients with mental illness in selected health facilities of Bangladesh - Shagoofa Rakhshanda; Labida Islam; Koustuv Dalal; Aklima Anwar Mitu; Farah Naz Rahman; Minhazul Abedin; Abrar Wahab; Cinderella Akbar Mayaboti; Salim M. Chowdhury; AKM Fazlur Rahman; Evan Atlantis; Saidur Rahman Mashreky (PLoS ONE, 2025)
The objective of this study was to explore the stigma among attendants (close relatives or other caregivers) who brought patients with mental illness to the selected mental health facilities in Bangladesh. This mixed-method study was part of a nationwide survey where respondents were conveniently selected. Cross-sectional data were collected from 176 attendants of patients with mental illness, and qualitative data were collected from 40 respondents. Quantitative data were collected in hand-held tablets using the Day’s Mental Illness Stigma Scale questionnaire. Qualitative data was collected in recorders, using a semi-structured guideline. The attendants had more stigma around the patients’ ability to maintain relationships, hygiene and discretion regarding their illness, with the highest level of stigma towards hygiene issues (score: 5.4). There was more positive attitude towards the treatability, curability, and recovery of the patients due to faith in the professional expertise of the service providers at mental health facilities, with the least level of stigma towards professional expertise (score: 6.4). Older people, females, and educated attendants were generally less stigmatized towards patients with mental illness than their counterparts. This study found that more stigma was present around the domains’ relationships, hygiene, anxiety, and visibility, while less stigma was present around the domains’ treatability, curability, and recovery of the patients. Further studies can be conducted to understand the effect of various factors on stigma, to aid in the development of interventions and counselling frameworks.